1996
DOI: 10.1063/1.166188
|View full text |Cite
|
Sign up to set email alerts
|

Infinite period and Hopf bifurcations for the pH-regulated oscillations in a semibatch reactor (H2O2–Cu2+–S2O2−3–NaOH system)

Abstract: Dynamic behavior of the pH-regulated oscillations has been studied for the hydrogen peroxide oxidation of thiosulfate ions in the presence of trace amounts of copper(II) ions in a semibatch reactor. A solution of 0.08 M Na(2)S(2)O(3) and 0.112 M NaOH was flowed at 0.160 mL/min into 300 mL of solution containing the H(2)O(2) and Cu(2+) in a vessel. There exists a critical value of the H(2)O(2) or Cu(2+) concentrations below which the system does not oscillate. The oscillations appear due to an infinite period b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…However, oscillatory behaviors or spatial pattern formations can be observed as transient phenomena during the course of relaxation to equilibrium [5][6][7][8][9]11,12]. Here, we address the following question: Can the formation of (transient) dissipative structures make far-from-equilibrium conditions last significantly longer by slowing down the relaxation process to equilibrium?…”
mentioning
confidence: 99%
“…However, oscillatory behaviors or spatial pattern formations can be observed as transient phenomena during the course of relaxation to equilibrium [5][6][7][8][9]11,12]. Here, we address the following question: Can the formation of (transient) dissipative structures make far-from-equilibrium conditions last significantly longer by slowing down the relaxation process to equilibrium?…”
mentioning
confidence: 99%
“…Qualitative analysis of time dependences of oscillation attributes at low and high oxygen concentrations suggests that at low oxygen concentrations oscillations disappear through the time-delayed Hopf bifurcation. 32,33 At high oxygen concentrations they disappear through the saddle node infinite period (SNIPER) bifurcation. 34 In the middle range of the oxygen concentrations (30-50%) we found that oscillations may disappear either through the time-depended Hopf or SNIPER bifurcations in unpredictable manner.…”
Section: Resultsmentioning
confidence: 99%
“…Time-delayed Hopf bifurcation 32,33,36,37 In this case oscillations disappear through oscillations with finite period and zero amplitude. Time dependences of oscilla-tion period and amplitude are characterized by the following laws in a vicinity of the moment of time when oscillations disappear: 32…”
Section: Simulations and Analysismentioning
confidence: 99%
“…In order to investigate the contribution of individual reaction steps to the overall dynamics and characterize bifurcation types in the model, two methods were applied: the method of numerical continuation [43][44][45][46][47] and the method proposed by Maselko 48 and other authors [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] for examination of bifurcations in oscillatory chemical reaction systems. The numerical continuation method was applied to each rate constant separately, keeping all other rate constants fixed.…”
Section: B Bifurcation Analysismentioning
confidence: 99%